Electric machines : modeling, condition monitoring, and fault diagnosis - Toliyat, Hamid A. (Boca Raton, Fla. : CRC Press, 2013)
'Preface The development of the electric motor is one of the greatest achievements of the modern energy conversion industry. Countless electric motors are being used in our daily lives for critical service applications such as transportation, medical treatment, military operation, communication, etc. However, due to the fundamental limitations of material life time, deterioration, contamination, manufacturing defects, or damages in operations, an electrical motor will eventually go into failure mode. An unexpected failure might lead to the loss of valuable human life or a costly standstill in industry, which needs to be prevented by precisely detecting or continuously monitoring the working condition of a motor. This book was written to provide a full review of diagnosis technologies and an application guide for graduate and senior undergraduate students in power electronics discipline who want to research, develop, and implement a fault diagnosis & condition monitoring scheme for better safety and improved reliability in electric motor operation. Furthermore, electrical and mechanical engineers in industry are also encouraged to take portions of materials in this book as a reference to understand the fundamentals of fault cause and effect and to fulfill successful implementation'--
1. Introduction / Seungdeog Choi -- 2. Faults in induction and synchronous motors / Bilal Akin and Mina M. Rahimian -- 3. Modeling of electric machines using winding and modified winding function approaches / Subhasis Nandi -- 4. Modeling of electric machines using magnetic equivalent circuit method / Homayoun Meshgin-Kelk -- 5. Analysis of faulty induction motors using finite element method / Bashir Mahdi Ebrahimi -- 6. Fault diagnosis of electric machines using techniques based on frequency domain / Subhasis Nandi -- 7. Fault diagnosis of electric machines using model-based techniques / Subhasis Nandi -- 8. Application of pattern recognition to fault diagnosis / Masoud Hajiaghajani -- 9. Implementation of motor current signature analysis fault diagnosis based on digital signal processors / Seungdeog Choi and Bilal Akin -- 10. Implementation of fault diagnosis in hybrid electric vehicles based on reference frame theory / Bilal Akin -- 11. Robust signal processing techniques for the implementation of motor current signature analysis diagnosis based on digital signal processors / Seungdeog Choi.
Includes bibliographical references and index.
Mode of access : World Wide Web.
Keywords: Electric machinery -- Reliability; Machinery -- Monitoring; Machine parts -- Failures